ANALYSIS OF ELEMENTARY SCHOOL STUDENTS' REFLECTIVE THINKING ABILITIES WITH THE APPLICATION OF THE DIFFERENTIATION PBL MODEL IN THE SUBJECT OF SOCIAL SCIENCES - Rarasaning Satianingsih; Rosmiati Rosmiati; Selina Sugiono; Neni Hermita (Program Studi PGSD Universitas Flores, 2025)
Reflective thinking is an essential component in fostering critical awareness and problem-solving skills that are particularly needed in Social Science subjects. However, observations indicate that fourth-grade students still exhibit low levels of reflective thinking due to ineffective teaching methods and the lack of alignment between instructional delivery and students’ abilities. This study aims to analyze the reflective thinking abilities of elementary school students through the implementation of a Differentiated Problem-Based Learning (PBL) model in Social Science learning. This study employs a mixed-method approach, with data collected through tests and questionnaires to measure students’ reflective thinking skills before and after the implementation of the differentiated PBL model. The findings show a significant improvement in students' reflective thinking skills, where the model encouraged active participation, collaborative learning, and deep reflection in problem-solving processes. This study emphasizes the importance of integrating innovative learning models such as differentiated PBL to enhance students' reflective thinking abilities and to promote meaningful Social Science learning at the elementary school level.